Impact of varying debris cover thickness on ablation: a case study for Koxkar Glacier in the Tien Shan - Juen, M.; Mayer, C.; Lambrecht, A.; Han, H.; Liu, S. (The Cryosphere, 2014)
To quantify the ablation processes on a debris covered glacier, a simple distributed ablation model has been developed and applied to a selected glacier. For this purpose, a set of field measurements was carried out to collect empirical data. A morphometric analysis of the glacier surface enables us to capture statistically the areal distribution of topographic features that influence debris thickness and consequently ablation. Remote-sensing techniques, using high-resolution satellite imagery, were used to extrapolate the in situ point measurements to the whole ablation area and to map and classify melt-relevant surface types. As a result, a practically applicable method is presented that allows the estimation of ablation on a debris covered glacier by combining field data and remote-sensing information. The sub-debris ice ablation accounts for about 24% of the entire ice ablation, while the percentage of the moraine covered area accounts for approximately 32% of the entire glacierized area. Although the ice cliffs occupy only 1.7% of the debris covered area, the melt amount accounts for approximately 12% of the total sub-debris ablation and 2.5% of the total ablation respectively. Our study highlights the influence of debris cover on the response of the glacier terminus in a particular climate setting. Due to the fact that melt rates beyond 0.1 m of moraine cover are highly restricted, the shielding effect of the debris cover dominates over the temperature and elevation dependence of the ablation in the bare ice case.